Pattern of Women Entrepreneurs in Gujarat’s Micro or Small Enterprises (International Journal of Scientific Research in Science and Technology, 2025)
Entrepreneurship plays a crucial role in economic growth, innovation, social transformation and impacts of different aspects of life of the people of the concerned area. In fact, traditionally the woman has been marginalized in the society by confining them to reproductive roles without recognizing their economic potential. However, advancements in technology, the desire for social and economic independency, and the flexibility of entrepreneurial work schedules have increased the participation rate of women to establish their own businesses. All these facts have drawn the attention of several scholars from different disciplines to carry on researches in the field entrepreneurship. This paper is undertaken to study the status and pattern of participation of women in micro and small enterprises in India and Gujarat. This study is entirely based on the secondary data collected by different sources published by MSME and NSSO as well as, academic articles, government documents, and other relevant literature. The analysis of data is done by employing percentage statistical technique. To support the analysis pie charts, line graph and bar diagrams as cartographic tools have also been employed to arrive at meaningful findings and conclusions towards futuristic plans and policies.